A Comparative Study of the Sounds of European and Brazilian Portuguese: Phonemes and Allophones - Massini-Cagliari, Gladis [UNESP]; Cagliari, Luiz Carlos [UNESP]; Redenbarger, Wayne J. (Wiley, 2016)
This chapter focuses on the sounds of Brazilian Portuguese (BP) with special attention given to the Paulista dialect. When European Portuguese (EP) presents noticeable differences from BP the author provides appropriate comments and examples in the chapter. BP has 21 consonantal phonemes. All these consonants appear in the word-initial syllable onsets, except the palatals and tap, which are found only word-internally. At the phonetic level, other consonants appear, as a result of the application of various phonetic processes. One of the most salient differences between BP and EP is the occurrence in EP of the unstressed tense vowel, where BP uses the lax vowel. A striking feature of EP when compared with BP is the greater occurrence of voiceless vowels. In BP, voiceless vowels are only found in word-final position before pause, and not always then. In EP they are regularly found in that and other contexts.
Keywords: Affricates; Allophones; Fricatives; Nasal consonants; Nasal vowels; Nasalized vowels; Palatal sonorants; Phonemes; Stressed vowels; Unstressed vowels